2008
DOI: 10.1016/j.bbadis.2008.02.001
|View full text |Cite
|
Sign up to set email alerts
|

The impact of mitochondrial tRNA mutations on the amount of ATP synthase differs in the brain compared to other tissues

Abstract: The impact of point mutations in mitochondrial tRNA genes on the amount and stability of respiratory chain complexes and ATP synthase (OXPHOS) has been broadly characterized in cultured skin fibroblasts, skeletal muscle samples, and mitochondrial cybrids. However, less is known about how these mutations affect other tissues, especially the brain. We have compared OXPHOS protein deficiency patterns in skeletal muscle mitochondria of patients with Leigh (8363G>A), MERRF (8344A>G), and MELAS (3243A>G) syndromes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 41 publications
2
34
0
Order By: Relevance
“…In contrast to conventional spectrophotometric assays, high-resolution respirometry permits the evaluation of the function of relatively intact, membrane-embedded respiratory complexes (Wenchich et al , 2003; Pecina et al , 2004; Stiburek et al , 2007; Fornuskova et al , 2008). The measurements were performed in the presence of carbonyl cyanide p -(trifluoromethoxy) phenylhydrazone (FCCP; an uncoupler of oxidative phosphorylation) as multiple substrate-inhibitor analyses.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to conventional spectrophotometric assays, high-resolution respirometry permits the evaluation of the function of relatively intact, membrane-embedded respiratory complexes (Wenchich et al , 2003; Pecina et al , 2004; Stiburek et al , 2007; Fornuskova et al , 2008). The measurements were performed in the presence of carbonyl cyanide p -(trifluoromethoxy) phenylhydrazone (FCCP; an uncoupler of oxidative phosphorylation) as multiple substrate-inhibitor analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Another T-to-C transition at nucleotide position 3271 occurred as a secondary common mutation [3] . The pathogenic mtDNA mutations can result in dysfunction of mitochondrial oxidative phosphorylation (OXPHOS) [22] , impairing respiratory capacity of the cell and ATP synthesis. Fornuskova et al [22] found that the 3243A→G frontal cortex mitochondria showed a marked loss of the complex IV holoenzyme, accompanied by accumulation of assembly intermediates.…”
Section: Ischemic Strokementioning
confidence: 99%
“…By far the most common finding in MELAS is complex I (CI) deficiency, whereas some patients have combined deficiencies of the RC CI, CIII, and CIV (13,14). Evidence from autopsy tissues suggest that RC complexes are differentially affected even in different tissues of one individual with m.3243A>G mutation with the CI deficiency dominating (15). Induction of nuclearencoded CII, succinate dehydrogenase (SDH), and mitochondrial accumulations in muscle and neurons are other typical findings in RC deficiencies (16,17), thought to be compensatory to the RC defect.…”
mentioning
confidence: 99%